High-Resolution in vivo Imaging of Xylem-Transported CO2 in Leaves Based on Real-Time 11C-Tracing - Hubeau, Michiel; Thorpe, Michael R.; Mincke, Jens; Bloemen, Jasper; Bauweraerts, Ingvar; Minchin, Peter E. H.; De Schepper, Veerle; De Vos, Filip; Vanhove, Christian; Vandenberghe, Stefaan; Steppe, Kathy (Frontiers in Forests and Global Change, 2019)
Plant studies using the short-lived isotope 11C have greatly advanced our knowledge about the allocation of recent photosynthate from leaves to sinks, but delivery of respired CO2 within the transpiration stream has been recognised as a second pathway of carbon supply to leaves. Here, we use in vivo tracing of xylem-transported 11CO2 to increase our knowledge on whole plant carbon cycling. We developed a new method for in vivo tracing of xylem-transported CO2 in excised poplar leaves using 11C in combination with positron emission tomography (PET) and autoradiography. We administered the tracer via the cut petiole and manipulated the transport by excluding light or preventing transpiration to show the applicability of both techniques in visualising and quantifying CO2 transport dynamics. Irrespective of manipulation, some tracer was found in main and secondary veins, little of it was fixed in minor veins or mesophyll, while most of it diffused out the leaf. Transpiration, phloem loading and CO2 recycling were identified as mechanisms that could be responsible for the transport pathways of internal CO2. Both 11C-PET and autoradiography can be successfully applied to study xylem-transported CO2, towards better understanding of leaf and plant carbon cycling, and its importance in different growing conditions.